DETERMINATION OF THIAMINE HCL (VITAMIN B1) AND PYRIDOXINE HCL (VITAMIN B6) CONTENT IN TABLET BY FTIR - Nugrahani, Ilma; Kartini, Citra (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The combination of thiamine hydrochloride (vitamin B1) with pyridoxine hydrochloride (vitamin B6) has been efficacious to help the metabolism of carbohydrates and amino acids. FTIR (Fourier transform infrared) is a technique widely used in compound identification and determination of functional groups but rarely used for the quantitative purposes. This study aims to obtain a analysis determination method of this vitamin combination simultaneously in tablet dosage form using FTIR. Methods: Amount of vitamin B1 and B6 standard were mixed with KBr crystal in a series of concentration (% w/w) in kalium bromide (kbr) crystal, then measured with FTIR. These spectrums yielded were transformed into an absorbance afterward changed to its derivative. The finest spectrum, which showed the best specificity and linearity, was selected and its area under the curve was calculated. The other validation parameters: accuracy, precision, detection limit, quantitation limit, and ranges, next were tested and determined. The validated method than was used to analyze the levels of vitamin B1 and B6 simultaneously in the tablets. Results: Vitamin B1 and B6 have the linear concentration range from 0.5 to 3.00% w/w. The regression equation for vitamin B1 is y = 0.0608 x-0.0176 with r = 0.9997 and Vx0 = 1.5047%, for vitamin B6: y = 0.0977 x+0.0079 r = 0.9995 and Vx0 = 1.7832%. Recovery results of vitamin B1: 98.98 to 100.93%, while B6: 99.06 to 100.43%. Intra-day and inter-day precision for vitamin B1: 1.73; 1.62; 1.48, and 0.58%, meanwhile for vitamin B6: 1.29; 1.60; 1.78, and 1.39%. The limits of detection and quantitation for vitamin B12 was 0.079 and 0.263% w/w respectively, and for vitamin B6, was: 0.093 and 0.311% w/w. The tablets from the market were tested showed the results that meet with compendia requirements. Conclusion: FTIR can be used for the determination of levels of vitamin B1 and B6 simultaneously in tablet dosage form and have met the validation requirements.